Posttraumatic growth following a drug-related death: A family perspective. Issue 5 (28th May 2023) - O'Callaghan, Daniel; Lambert, Sharon; Conway, Nora; Frost, Nollaig
Abstract: This paper explores the experience of posttraumatic growth in families who have lost a family member to a drug-related death. Seven family units (17 participants) were interviewed, and interviews were analyzed using reflexive thematic analysis. Analyses revealed themes that reflected positive adaptation and growth, including (a) reframing the loss, (b) open dialogue and social support, and (c) reclamation of purpose. Themes are presented in this paper for their pertinence in understanding how best to negotiate adaptation through complicated grief. The paper concludes that posttraumatic growth can occur once families begin a process of acceptance and receive support through the journey.